Enhanced UV Resistance of Poly(methyl methacrylate) Through Schiff Base and Metal Oxide Nanoparticle Incorporation - Hussein, Ahmed; Yousif, Emad; Rasheed, Malath; Ahmed, Dina; Bufaroosha, Muna; Kadhom, Mohammed (Universitas Gadjah Mada, 2025)
In this work, a novel poly(methyl methacrylate) (PMMA) material was prepared by incorporating Schiff base and metal oxide nanoparticles (NPs). Hence, different polymer derivatives were produced, and their resistance to light degradation was improved. PMMA was subjected to chemical modification, first by reacting PMMA with an excess of ethylene diamine to reduce the occurrence of cross-linking. Second, it underwent a reaction with the amino group of 4-methoxybenzaldehyde to produce Schiff base molecules. These molecules were subsequently infused with various metal oxide NPs, namely: TiO2, CuO, Cr2O3, Co2O3, and NiO to work as photostabilizers and prepare modified PMMA films. The synthesized polymers were analyzed using Fourier transform infrared (FTIR) and NMR spectroscopy to confirm their structures and determine the extent of structural alterations. FTIR and weight loss measurements assessed modified PMMA's UV stabilization. The effectiveness of functional groups was assessed by monitoring their growth. Additional analyses were done included atomic force microscopy (AFM), scanning electron microscopy (SEM), and microscopic imaging. Unmodified PMMA performed worse than Schiff base polymers. The modified PMMA photodegraded less than the blank films after 300 h of UV exposure. The unit's strong internal conjugation absorbs UV light, which improves performance.